Banking in transition countries - John Bonin; Iftekhar Hasan; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
Modern banking institutions were virtually non-existent in the planned economies of cen-tral Europe and the former Soviet Union. In the early transition period, banking sectors be-gan to develop during several years of macroeconomic decline and turbulence accompa-nied by repeated bank crises. However, governments in many transition countries learned from these tumultuous experiences and eventually dealt successfully with the accumulated bad loans and lack of strong bank regulation. In addition, rapid progress in bank privatiza-tion and consolidation took place in the late 1990s and early 2000s, usually with the par-ticipation of foreign banks. By the mid 2000s the banking sectors in many transition coun-tries were dominated by foreign owners and were able to provide a wide range of services. Credit growth resumed, sometimes too rapidly, particularly in the form of lending to households. The global financial crisis put transition banking to test. Countries that had expanded credit rapidly were vulnerable to the macroeconomic shock and there was con-siderable concern that foreign owners would reduce their funding to transition country sub-sidiaries. However, the banking sectors turned out to be resilient, a strong indication of the rapid progress in institutional development and regulatory capabilities in the transition countries.
URN:NBN:fi:bof-201408071915
Keywords: G21; P27; O57; 330; transition banking; bank privatization; foreign banks; bank regulation; credit growth